Reflective Leadership Practice for Academic Chairs - Sue Wells; Marilyn Herie (Academic Chairpersons Conference Proceedings, 2018)
This workshop distills the practice wisdom of two seasoned academic leaders, providing a menu of reflective leadership practice activities, tools for eliciting feedback from others, and practical tips for creating a high-functioning and positive departmental culture, illustrated throughout with personal leadership stories and case examples.
Keywords: Academic Leadership; Reflective Practice; Leadership Development; High-performing Teams; Leadership Values